Effects of injection parameters on performance of diesel engine run on biodiesel from direct transesterification / Tatagar Mohammad Yunus Khan - Tatagar Mohammad Yunus, Khan (2017)
It is well-known that energy consumption is rapidly increasing due to the population growth, higher standard of living and increased production. Significant amount of energy resources are being consumed by the transportation sector leading to the fast depletion of fossil fuels and environmental pollution. Biodiesel is one of the technically and economically feasible options to tackle the aforesaid problems. There are more than 350 oil-bearing crops identified as potential sources for biodiesel production around the globe. The wide range of available feedstocks for biodiesel production represents one of the most significant factors for producing biodiesel. The research work is carried out on fuel properties of biodiesel prepared from the non-edible oils of Nigella sativa. Nigella sativa is believed to be investigated for the first time as a biodiesel feedstock. Biodiesel seems to be a replacement to the diesel, can be commonly produced by esterification-transesterification. In the current research a new method i.e. direct transesterification is developed and compared it with conventional esterificationtransesterification. The fuel properties of biodiesel produced by both methods are investigated and compared. Though there are no significant differences in the fuel properties obtained from either of the methods but the acid value of biodiesel and reaction time reduced significantly besides improved biodiesel yield by direct transesterification method. The direct transesterification method was further improved to modified direct transesterification method for minimizing the time required for biodiesel separation from glycerol and blending of diesel and biodiesel. Today’s automobiles require economy of operation, high power output and last but not the least, reduction in greenhouse gases emitted by the vehicles. Such specific demands have compelled the researchers not only to focus on the parameters affecting the performance but also on emission of the internal combustion engines. The current research has been focused and optimized the injection timing of 270BTDC and injection pressure of 240bar for selected diesel engine for the maximum possible efficiency and lower exhaust emissions for an internal combustion diesel engine run on biodiesel fuels.